MELACAK PEMIKIRAN AL-ALUSI DALAM TAFSIR RUH AL-MA’ANI - Setianingsih, Yeni (IAIN Tulungagung, 2017)
Every exegesis book has its own special characteristic in accordance with the result of Interpreter?s thinking, and every interpreter has his own tendency in accordance with the scope of social setting. Moreover, owing to expanding science, and the more strong of judgement from interpreters, more and more it makes the work of exegesis has inclination to the scientific or the science specialization in accordance with each owned ability. It is likewise happened to Al-Alûsî in his exegesis, Rûh al-Ma?ânî. The involvement of Al-Alûsî in mysticism field since he was child, also makes his exegesis has sufismystic nuance. Nevertheles, ra?yi?s substance is still felt strong in his exegesis. The way of his work in interpreting the holy Qur?an certainly is not apart from his first idea about the concept of Qur?an, tafsir, and ta?wîl. Because of the explaining about the three trams, it can be known what it makes Al-Alûsî ?s criterion in interpreting the holy Qur?an. Keywords: Al-Alûsî , Rûh al-Ma?ânî, sufismystic.